PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN SEKTOR AGRICULTURE TAHUN 2012-2015 - SYAMSUL FAUZI, MUHAMMAD (Jurnal Ilmu Manajemen (JIM), 2018)
The purpose of this study is to know the influence of capital structure, firm size, and profitability to firm value. Agriculture sector companies period 2011-2015 are an object of this study. Sample used in this study amounted 16 companies using purposive sampling method. This study used causal associative approach which use secondary data obtained than documentation from official website of Indonesia Stock Exchange. Multiple regression linear is the analysis method used in this study. The result from this study show that capital structure and profitability negatively impact on firm size. Firm size on this study has no impact to firm size. Recommendations that be able obtained from result of these study is the company need to consider capital structure and profitability to maximize firm value. For investors need to consider capital structure and profitability as a sign or a hint which takes precedence before purchase companies stock at agriculture sector. Key word: capital structure, firm size, profitability, firm value